If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(180 + -1x) + -5 = x (180 * 6 + -1x * 6) + -5 = x (1080 + -6x) + -5 = x Reorder the terms: 1080 + -5 + -6x = x Combine like terms: 1080 + -5 = 1075 1075 + -6x = x Solving 1075 + -6x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1075 + -6x + -1x = x + -1x Combine like terms: -6x + -1x = -7x 1075 + -7x = x + -1x Combine like terms: x + -1x = 0 1075 + -7x = 0 Add '-1075' to each side of the equation. 1075 + -1075 + -7x = 0 + -1075 Combine like terms: 1075 + -1075 = 0 0 + -7x = 0 + -1075 -7x = 0 + -1075 Combine like terms: 0 + -1075 = -1075 -7x = -1075 Divide each side by '-7'. x = 153.5714286 Simplifying x = 153.5714286
| 11.3+-7.2f=-3.82 | | 48t+265=553 | | 5x+3=14x-42 | | F(x)=x^2-3x-4/x^2-25 | | 2x+2x+x+9+x+9=84 | | =3-4n+9 | | w-0.06w=26.32 | | [5-2x]+3=8 | | 3-3x=27 | | 6z+3z=72 | | 10r+100s+50r=0 | | (-16/8)-1/8 | | 4*8+9(3a+5)+8(2a+1)=0 | | -16/8-1/8 | | p^2-14=0 | | (3x+4)-2(x-4)=4(x+6)+5x | | 139*14= | | 5w+3=12+2w | | 16x^2-6x-5=0 | | .91Y+1=y-.8 | | 12(c+3d+4f)+2(2c+d+6f)=0 | | 7=3-5x+4 | | 8(r+15)+7(2r+10)=0 | | x+5x+8(x+2)=0 | | 5d=-1-24 | | 5(x+2y)+6x=0 | | n+(n+1)=269 | | 5-5[2-(3y-3)]= | | -24=-6w+3(w-5) | | (5x+2)m=131 | | (5x+3)m=131 | | 5(x+1)=2+5x |